A Comparison of Self-Reported Anxiety and Depression Among Undergraduate Music Majors and Nonmusic Majors. Issue 3 (June 2021) - Gilbert, Danni
The purpose of this exploratory research study was to compare anxiety and depression levels reported by music majors and nonmajors at a small, private liberal arts university. Study participants completed the Burns Anxiety Inventory and Burns Depression Checklist. Anxiety and depression levels were significantly higher among music majors, and there was a strong, positive relationship between anxiety and depression. Regardless of major, self-reports were not affected by year in school. Implications for additional mental health resources and strategies for improving music major health and self-care are discussed, along with a need for increased music faculty awareness of perceived anxiety and depression leading to modified programs of study.